STANDARDISASI VS ADAPTASI BAURAN PEMASARAN GLOBAL PERUSAHAAN MULTINASIONAL - ASEP HERMAWAN (Jurnal Bisnis dan Akuntansi, 1999)
The paper marketing theories underlying standardization or adaptation and also discusses empirical articles about the controversy on these issues and directions for futher research are also proposed.